Analisis Faktor Determinan Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Terapi Hemodialisis - Siprianus Abdu; Yunita Carolina Satti (Jurnal Keperawatan Florence Nightingale, 2024)
Chronic kidney failure is a slow, long, persistent kidney failure that results in a buildup of metabolic waste so that the kidneys cannot meet their usual needs. GGK patients usually undergo hemodialysis therapy to replace damaged kidney function thereby improving the patient's quality of life. Quality of life is an individual's perception related to goals, expectations, standards and problems. The purpose of the study was to find out the factors that affect the quality of life of GGK patients undergoing hemodialysis therapy, the study was conducted at Stella Maris Hospital Makassar in September 2023. This type of research is an analytical observational design with a cross-sectional study approach. The sampling technique is nonprobability sampling with a total sampling approach with a total sampling approach with a total of 45 respondents. The instruments used are quality of life questionnaires and family support questionnaires. The hypothesis test in this study is the Chi-Square test which if met is read in Pearson Chi Square if it is not continued with the Kolmogorov Smirnov test. The results concluded that of the 5 factors studied, there are 3 factors related to quality of life, namely age (p = 0.015), education (p = 0.001), family support (p = 0.000) while there are 2 factors that are not related to quality of life, namely gender (p = 0.485), and occupation (p = 0.216). The results of this study are expected to improve the quality of life of GGK patients undergoing hemodialysis therapy.